Reduction of Waste Caused by Defective Bottle Caps in Bottled Water Manufacturing - สุวรรณ, ศุภลักษณ์; พลเดช, ลิขิต (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to analyze the causes of defective bottle caps in the capping process of bottled drinking water production and to develop improvement measures to reduce the defect rate. The study employed a process improvement research approach, which included defect data collection from the production line, root cause analysis using quality control tools, and the design and implementation of corrective actions. The results of the pre-improvement analysis indicated that the primary causes of bottle cap defects were the improper adjustment of the cap feeder rail angle, which caused caps to flip upside down, inconsistent capping pressure at the capping station, and the absence of an in-process inspection system. Quality control tools used in the analysis included Pareto charts, cause-and-effect (fishbone) diagrams, and control charts. To address these issues, a cap inversion prevention device was designed and installed. The device consisted of a star wheel mechanism, detection sensors, and an air cylinder system to identify, separate, and remove incorrectly oriented caps before they entered the capping head. In addition, the cap feeder rail angle was adjusted to ensure proper cap orientation and smooth feeding into the capping process. The results of the post-improvement evaluation revealed that the defect rate decreased to 0.16, corresponding to a 12.43% reduction when compared with the pre-improvement stage, demonstrating that the developed device and feeder rail adjustment significantly improved the effectiveness and reliability of the capping process. The proposed improvements enhanced product quality consistency, reduced production costs, and can be applied to similar production processes in the bottled drinking water industry and related manufacturing sectors.